Cysteine‐rich protein 61, a specific ultra‐early biomarker in kidney ischemia/reperfusion injury. Issue 8 (2nd May 2019) - Li, Chenyu; Zhao, Long; Wang, Yanfei; Che, Lin; Luan, Hong; Luo, Congjuan; Xu, Yan
ABSTRACT: Aim: Studies have shown that cysteine‐rich protein 61 (Cyr61) increased in the post‐ischemic human kidney tissue. However, it is still unknown whether Cyr61 can be used as a biomarker in kidney ischemia/reperfusion (I/R) injury. Methods: Microarray data were collected from GSE58438 and GSE52004. The rat I/R model was established to evaluate the messenger RNA and protein expression of Cyr61, localization of Cyr61 by immunohistochemical and immunofluorescence staining, and changes in serum creatinine (Scr) at the same time. Results: Bioinformatics result showed that Cyr61 was significantly increased at 3 h after I/R in rat kidney, and involved in angiogene, positive regulation of locomotion and single organism cell adhesion. The rat I/R model results showed that Cyr61 was mainly expressed in renal tubular epithelial cells with I/R injury and the expression of Cyr61 was up‐regulated at I/R 1 h, peaked at 4–8 h and began to decay at 12 h. The area under curve of receiver operating characteristics of kidney tissue Cyr61 messenger RNA and urine Cyr61 were 90.2% and 86.1%, which all better than Scr 67.1% ( P  < 0.05). Conclusion: We made a preliminary investigation of the relationship between Cyr61 and AKI, which identifies that Cyr61 may replace Scr as an ultra‐early new biomarker in AKI. SUMMARY AT A GLANCE: Although Cystatin C (CysC) was recommended by some authors to be measured in addition to creatinine in glomerular filtration rate estimation, it has found its place in early detection of acute kidney injury after ischaemia/reperfusion injury in rat kidney.